Usaha Kuliner Kreatif Prospek dari Strategi Pemasaran Syariah Pasca Pandemi Covid-19 Kota Jambi - Ana Catur Wulandari (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
This thesis aims to find out what are the impacts of the Covid-19 outbreak on Creative Culinary MSME business actors d, the obstacles faced by Creative Culinary MSME business actors, to find out business conditions in the post-Covid-19 and post-pandemic period, and how a form of marketing strategy carried out for business actors in order to maintain their business during the Covid-19 pandemic and in the Post-Covid-19 pandemic. This type of research is a field research (Field Research) with a qualitative approach. Methods of collecting data in this research by conducting observations, interviews, documentation and drawing conclusions. The results of this study indicate that the Covid-19 pandemic has greatly impacted MSMEs. Where the impacts experienced include: (1) Business conditions during the pandemic decline and in the post-pandemic period there is still a recovery period for businesses, (2) Obstacles in implementing marketing strategies, (3) Declining levels of people's purchasing power due to reduced community activities outside house. (4) Decreased sales turnover. There are several efforts by business actors to increase income during the pandemic and post-pandemic, during this pandemic by utilizing technology and providing discount promos for sales through applications, providing good service and maintaining cleanliness by always complying with Health protocols. , and pay attention to the quality of goods to be sold to consumers, without reducing taste and fraud in producing a product. And after the pandemic, Creative Culinary MSME entrepreneurs have remained the same in the past, always maintaining existing marketing strategies, in order to survive and continue to try to attract consumers to increase consumer purchasing power, the aim of which is the business prospects that are being carried out, besides that business actors must compete against other business actors in their own way without violating Islamic laws.